Exeinai und exousia. Ein frühes Kapitel aus der Geschichte der Freiheitsidee - Stemmer, Peter (Phronesis, 2023)
AbstractThe term exeinai expresses the fact that it is open to someone to act in a certain way. It refers to the ideas of alternative possibilities, being able and having been able to act otherwise and having the power to act on one’s own. Exousia is closely related to eleutheria, freedom, and from Aristotle onwards exeinai is also related to the notion ep’ autō(i), being up to someone. This paper is the first detailed study of the usage, the conceptual connections and the significance of exeinai and exousia in Plato, Aristotle and Epictetus, and it aims to shed new light on an early phase in the history of the idea of freedom.